Software Architectures for Serious Game Development. A Systematic Literature Review - Sandí Delgado, Juan Carlos (2026)
This article brings together the results obtained through a systematic review of literature, in which both sources and a novel methodology are used to analyze and compare software architectures proposed for the development of video games, in particular, serious games oriented to the formation of technological competencies. A complex and exhaustive analysis of 13 architectural proposals was carried out in light of a systematic review protocol, which integrates categories and criteria that allow them to be analyzed according to the study's objective. Four categories were defined: a- General aspects, b- Architectural aspects, c- Pedagogical aspects, and d- Analysis aspects. The results showed that the architectural proposals had been mostly designed for their use at the higher education/university level. The results also made evident that the architectural proposals were executed as web applications in which their reuse of components is considered significant. They were mainly used to develop video games at a general level. It is concluded that an architectural proposal for the development of serious games as such is not identified. However, based on the results obtained, a checklist has been prepared with the primary considerations that software developers could consider when implementing an architectural design for a serious game. This checklist holds a pedagogical intention to form technological skills which will be relevant and transcendent at a national and international level for video game developers by providing a research baseline.